SISTEM INFORMASI PENGOLAHAN DATA TINDAK KRIMINALITAS PADA POLRESTA JAMBI: Application, Criminal, Data Processing, Data, Website - Nurjani, Yeni; Heranda, Dufan (LP2M Universitas Nurdin Hamzah, 2025)
The use of information technology in the National Police, such as the Criminal Investigation Information System application at the Jambi City Police, helps in processing police report data and handling criminal cases. However, challenges still exist because data processing is still manual, creating delays in reporting and investigating cases. Therefore, an application was created,